Association between serum cortisol and progesterone concentrations and the infiltration of immune cells in the endometrium of gilts with vaginal discharge - Atthaporn Roongsitthichai (2018)
The objective of the study was to investigate an association between serum cortisol and progesterone (P 4 ) concentrations and the distribution of immune cells in the endometrium of the gilts with vaginal discharge. Genital organs from 39 Landrace×Yorkshire crossbred gilts culled owing to vaginal discharge problem were collected from two commercial swine herds in Thailand. The estrous stage and gross pathology were examined. Blood samples were collected from the jugular vein prior to being slaughtered. Serum P 4 and cortisol were analyzed by means of enzyme immunoassay. The samples observed were in inactive (n=4), follicular (n=10), and luteal (n=25) phases. They, afterwards, were processed in hematoxylin and eosin sections. The endometrium of the gilts was histologically divided into three layers, i. e., epithelial, subepithelial connective tissue, and glandular connective tissue layers. Immune cells, i. e., lymphocytes, neutrophils, eosinophils, macrophages, and plasma cells, in each layer were quantified under a light microscope (×400). The results revealed that mean serum cortisol was 430.6±68.3 nmol/l. Serum P 4 varied by ovarian status. Serum P 4 of the gilts in the luteal phase was higher than those in the follicular phase (88.3±7. 7 versus 20.6±6.2 nmol/l, P < 0.05). As for the endometrium condition, the gilts were classified into acute/subacute endometritis (n=13), chronic endometritis (n=9), and normal endometrium (n=17). Neutrophils were the main local immune cells in the epithelial layer. Lymphocytes were the dominant population in the subepithelial and glandular connective tissue layers. Generally, the serum cortisol tended to negatively correlate with lymphocytes in the subepithelial connective tissue layer (r=-0.28, P=0081). In the gilts with acute/subacute endometritis, no correlation among serum cortisol, P 4 , and immune cells was observed. In chronic endometritis gilts, only a negative correlation was remarked between P 4 and epithelial lymphocytes (r=-0.83, P=0.010), epithelial neutrophils (r=-0.79, P =0.019), and subepithelial neutrophils (r=-0.73, P=0.025). In the gilts with normal endometrium, P 4 negatively correlated with subepithelial neutrophils (r=-0.55, P=0.022) while positively correlated with subepithelial macrophages (r=0.54, P=0.024) and subepithelial eosinophils (r=0.60, P=0.011). © 2010 Springer-Verlag London Limited.